The Effect of Working Capital Management and Financial Literacy Mediated by Financial Inclusion on The Financial Performance of Poklahsar in Padang City - Candra, Eka; Zulvia, Yolandafitria (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
This article aims to measure the extent to which financial performance is influenced by working capital management and financial literacy mediated by financial inclusion of POKLAHSAR in Padang City. Based on the characteristics of the problem and the objectives of this study, it is a quantitative study, namely the data used is in the form of numbers. Quantitative research emphasizes testing theories through measuring research variables with numbers and analyzing data with statistical procedures. This study observes the factors that influence the financial performance of POKLAHSAR. This study aims to explain the influence of independent variables mediated by mediating variables on dependent variables. The population is 65 groups and is equal to the sample which is also 65 groups spread across 9 Districts in Padang. The sampling technique used is saturated sampling. Working Capital Management does not have a significant influence on Financial Performance, and it also has very little influence on Financial Inclusion. Financial Literacy does not have a significant effect on financial performance. Likewise, the effect of Financial Literacy on Financial Inclusion. Financial Inclusion has a significant influence on financial performance.